The Influences of Books of Manners and Dedekind's Grobianus on John Gay's Trivia. - Patton, William Wesley (Journal of Language, Literature & Culture, 2021)
For decades critics have categorised John Gay's Trivia: or The Art of Walking the Streets of London as a mock Georgic deriving its main characteristics and themes from Juvenal's Third Satire and Virgil's Georgics. Many readers have been perplexed by the ambiguities and dissonance between the Walker's/Author's observations, advice, and actions and the characteristics of those classical genres. This article discusses the additional influences of civility books, especially Dedekind's German satiric civility book, Grobianus, on Trivia. Those literary lineages place in context the Walker's inconsistently ironic advice and explain how Gay uses the distinction between the Walker's advice and his contrary behaviour to describe the psychological and pragmatic complexities of a shift from rural to urban lifestyles.